Controlling the motion of hydrogen molecules - Procter, SR; Yamakita, Y; Merkt, F; Softley, T (2003)
The deflection and deceleration of neutral hydrogen molecules in the presence of an inhomogeneous electric field is demonstrated. The molecules are laser-excited in a molecular beam to selected Rydberg-Stark states in the field of an electric dipole for a fixed period, and their trajectories are monitored using ion imaging and time-of-flight measurement. The Rydberg states (n≈17) show remarkably long lifetimes (>100 μs) and these results point to a novel method for trapping and cooling non-polar, non-magnetic molecules. © 2003 Elsevier Science B.V. All rights reserved.